"Magic" Surface Clustering of Borazines Driven by Repulsive Intermolecular Forces1. Issue 29 (4th June 2013) - Kervyn, Simon; Kalashnyk, Nataliya; Riello, Massimo; Moreton, Ben; Tasseroul, Jonathan; Wouters, Johan; Jones, Tim S.; De Vita, Alessandro; Costantini, Giovanni; Bonifazi, Davide
<x xml:space="preserve">Abstract</x> It's a kind of magic: Hydroxy pentaaryl borazine molecules self‐assemble into small clusters (see structure) on Cu(111) surfaces, whereas with symmetric hexaaryl borazine molecules large islands are obtained. Simulations indicate that the observed "magic" cluster sizes result from long‐range repulsive Coulomb forces arising from the deprotonation of the BOH groups of the hydroxy pentaaryl borazine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>